TEACHERS’ AGE IN RUSSIAN HIGHER EDUCATION INSTITUTIONS: WHAT IS THE PROBLEM? - Victoria F. Pugach (Высшее образование в России, 2017)
Abstract. The paper proposes an approach to the estimation of university professors’ age. Its purpose is to analyze the median age of teachers in Russian universities and identify problems relating to the teacher age structure. The paper considers various factors affecting teachers’ median age, such as the median age of employees in economics, average number of years of study, teaching staff job structure. There is a trend to the median age decrease for teachers on lower positions and the median age increase for teachers on top positions in a job structure. There is given the median age of teachers on certain positions, a teacher career ladder is proposed with estimated waiting periods for the next job position. The paper concludes that professional stability of middle-aged teachers is low, leading to polarization and thinning of the middle layer in teacher age structure, and this is the main problem.